Verification of the Effectiveness of Risk Communication Materials Using Natural Radiation Levels as a Reference Standard: Results from a Survey of First-Year Health Department Students - Hiromi Kudo; Masahiro Hosoda; Yasutaka Omori; Kazutaka Tanaka; Minoru Osanai; Takashi Ohba; Isamu Amir; Masaharu Tsubokura; Shinji Tokonami (Safety)
Even before the Fukushima Daiichi Nuclear Power Plant accident, people were continuously exposed to various naturally occurring radioactive materials, including radon. However, public awareness and understanding of this exposure remain limited. When communicating the risks of radiation exposure from the Fukushima accident, explanatory materials have not typically incorporated data from coastal areas of Fukushima Prefecture collected after the incident to clarify the actual levels of artificial and natural radiation exposure. This study aimed to assess whether presenting radiation dose data from coastal areas of Fukushima Prefecture—using natural radiation as a reference point—could influence risk perception regarding the health effects of radiation exposure and its potential impact on future generations. The study focused on students enrolled in health science-related departments at Hirosaki University. Before being presented with the data, the students had limited understanding of radiation. However, after reviewing the explanatory materials, 89 students (48.4%) demonstrated an improved understanding of its potential impact on future generations, while 87 students (47.3%) showed increased awareness of the effects on their own health. Regarding the reduction in risk perception, many students attributed it to the fact that radiation levels 10 years after the Fukushima nuclear accident were not significantly different from natural background radiation in most areas. These findings suggest that providing actual radiation measurement data from affected areas can significantly influence risk perception and decision-making processes. The results indicate that participants became more aware of the presence of natural background radiation, and the comparison with current radiation levels in Fukushima played a key role in shaping their risk perception.